Neuroprotective potential of astroglia. Issue 11 (24th August 2017) - Liu, Beihui; Teschemacher, A. G.; Kasparov, Sergey
Abstract : Astroglia are the homoeostatic cells of the central nervous system, which participate in all essential functions of the brain. Astrocytes support neuronal networks by handling water and ion fluxes, transmitter clearance, provision of antioxidants, and metabolic precursors and growth factors. The critical dependence of neurons on constant support from the astrocytes confers astrocytes with intrinsic neuroprotective properties. On the other hand, loss of astrocytic support or their pathological transformation compromises neuronal functionality and viability. Manipulating neuroprotective functions of astrocytes is thus an important strategy to enhance neuronal survival and improve outcomes in disease states. © 2017 The Authors Journal of Neuroscience Research Published by Wiley Periodicals, Inc.